2006
DOI: 10.1093/intimm/dxl030
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of mucosal immune cells to methotrexate-induced mucositis

Abstract: The use of high doses of the anti-cancer drug methotrexate (MTX) is associated with intestinal damage. As a result, mucosal immune cells become increasingly exposed to a vast amount of microbial stimuli. We aimed at determining whether these cells are still functional during MTX treatment. Furthermore, we assessed if activation of the mucosal immune system would play a role in the pathogenesis of mucositis. A contributive role to mucositis for the adaptive immune system was established by showing that mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 22 publications
3
61
0
1
Order By: Relevance
“…Thus, the effects of CPT-11 were compartmentalised with a primed local intestinal immunity and concomitantly suppressed systemic immunity. Our results are consistent with earlier findings (de Koning et al, 2006) that innate and adaptive immune responses of GALT cells were intact or even primed after high-dose methotrexate. CPT-11 has been consistently shown to disrupt GI integrity, and this may expose GALT cells to bacterial antigens and LPS.…”
Section: Hyper-responsive State Of Mln Cellssupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, the effects of CPT-11 were compartmentalised with a primed local intestinal immunity and concomitantly suppressed systemic immunity. Our results are consistent with earlier findings (de Koning et al, 2006) that innate and adaptive immune responses of GALT cells were intact or even primed after high-dose methotrexate. CPT-11 has been consistently shown to disrupt GI integrity, and this may expose GALT cells to bacterial antigens and LPS.…”
Section: Hyper-responsive State Of Mln Cellssupporting
confidence: 94%
“…CPT-11 has been consistently shown to disrupt GI integrity, and this may expose GALT cells to bacterial antigens and LPS. Hyper-responsiveness of intestinal local immune cells is considered to contribute to chemotherapy-induced gut injury (de Koning et al, 2006). Antigen-driven T-cell expansion in GALT may support the homeostasis of T-cell pools after depletion by chemotherapy (Dulude et al, 1997).…”
Section: Hyper-responsive State Of Mln Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 is one of the more researched anti-inflammatory cytokines in mucositis. DeKoning and colleagues demonstrated that IL-10-deficient mice experience an increased weight loss and more severe intestinal damage following methotrexate treatment in comparison to wild-type controls [55]. Furthermore, cytokines directed at inhibiting pro-inflammatory cytokines may be useful as interventions for mucositis [56].…”
Section: Inflammationmentioning
confidence: 99%
“…Chemotherapy is known to be capable of inducing an inflammatory cytokine response, which can lead to cytokine-induced sickness [27,42]. High dose MTX can induce mucositis, which is characterized by damage to the gastrointestinal mucosa [7]. This leads to a decreased barrier function and an enhanced risk of developing infections caused by micro-organisms originating from the intestines.…”
Section: Introductionmentioning
confidence: 99%